Kekuatan Pembuktian Surat Letter C Dalam Pemeriksaan Sengketa Tanah di Persidangan - Annisa Oktaviani; Harjono, S.H., M.H - (Sebelas Maret University, 2019)
This study aims to determine the strength of evidence of Letter C fled by the Plaintiff in court and the appropriateness of judges’ consideration in applying Government Regulation No.24 of 1997 on Land Registration. This legal research is a doctrinal or normative legal research that is descriptive. The research approach used in the writing of this law, the case study (case study). Sources of legal materials using primary legal materials and secondary legal materials. The technique of collecting legal materials is done by literature study or document study. The technique of analysis of law materials is a deductive method of syllogism. The results and discussions indicate that Letter C or quotation of Letter C can not be used as evidence in court if it is not accompanied by other evidence and the strength of the proof is left to the judge’s consideration. Judge consideration in deciding the land case must be in accordance with the regulation Government Regulation Number 24 of 1997 concerning Land Registration.Keywords: Letter C, evidence of Letter C, Land Registration